Advantage Of Installing Moodle Learning Management System Under Iis/Mariadb Over Apache/MySQL - Poghosyan, Irina (Զանգակ հրատ.)
This article examines the advantages and disadvantages of installing Moodle's popular learning management system using MySQL, MariaDB, Apache, and Internet Information Services. It considers the impact of these choices on performance, database server speed, and cyber security, which is critical for dealing with many users and students whose numbers have increased dramatically since the onset of the global pandemic caused by the SARS-CoV-2 virus. It has been determined that IIS/MariaDB represents the optimal configuration for Windows-based systems, while Apache/MySQL is optimal for Linux distributions. The selection of specific solutions should be based on the particular needs of the educational institution in question, the available infrastructure, and the financial capabilities of the institution in question. MariaDB's functionality is enhanced by including the Galera Cluster, which offers a higher throughput than MySQL's. Both IIS and Apache have some advantages and disadvantages. The decision to use one or the other is made based on the choice of operating system.
Keywords: Education